An Endless Bargain: A Participatory Approach to Understanding Intra-household Finance. (September 2022) - Gupta, Shriyam; Yagnaraman, Dhwani; Jagati, Aditya
While factors influencing intra-household dynamics, preferences of individual members, and their impact on household financial decision-making have been studied, the actual process of bargaining, and decision-making process remain uncaptured. We take a qualitative approach to address this gap and do so in two distinct ways. We first conduct a photo elicitation session (n = 55) to understand gender differences in financial responsibility, dynamics in purchase and saving decisions, and conflict resolution. Then, using findings from the photo elicitation, we develop a gamified instrument to observe financial decision-making in real-time between couples (n = 32). We find that husbands and wives have separate spheres of responsibility within the household, which determine their financial decision-making ability. Further, we find that income, investment and children motivate "big" financial expenditures, while savings is understood as an act of cutting expenses. Finally, we discuss the opportunities to employ new qualitative methods to study and capture behavioral dynamics. JEL Codes: D130, G510, G59